Parents' Support With Independence In Online Learning For Preschool Children (4-6 Years) - Ishariani, Linda; Siswoaribowo, Andika; Indah, Fitri Sri (Journal of Applied Nursing and Health, 2023)
Background: Parental support with independence in online learning for preschool-aged children (4-6 years). Support is needed in the form of emotional support, informative support, instrumental support, appraisal support, or awards. This study aims to determine parental support for independence in online learning for preschool-aged children (4-6 years). Methods: This study uses a design non Experimental with the Correlational research design and through the approachCross Sectional. The sample of this research is TPA Alfassalam students totaling 30 respondents with techniqueTotal Sampling. Respondent data collection uses a questionnaire in the form of a Google form link. Data were analyzed using the Spearman level test. Results: The results showed that almost all respondents (83.3%) had parental support in the good category, while the level of independence for most (73.3%) was in the good category. The results of the Spearman rank analysis show that p-value = 0.000 with a = 0.05 and the value of the Coefficient Correlation (r) is 0.742, including the level of the strong relationship and the direction of a positive relationship where the better parental support, the better the child's independence in online learning. Conclusion: There is a relationship between parental support and independence because many parents are broad-minded. Therefore, optimal parental support is needed so that children are always enthusiastic about learning online and that it is useful when they grow up.